Liver stiffness value obtained with ElastPQ ultrasound increases with NYHA class in chronic heart failure patients and reduced ejection fraction - Yahya Kemal İçen; Abdullah Orhan Demirtaş; Ayşe Selcan Koç; Hilmi Erdem Sümbül; Mevlut Koç (KARE Publishing, 2019)
Objective: Liver stiffness (LS) values are known to be associated with increased right ventricle (RV) pressure in patients with heart failure (HF). The aim of this study was to determine the changes in LS in patients of different New York Heart Association (NYHA) classes and the parameters related to increased LS in HF patients with reduced ejection fraction (HFrEF). Methods: A total of 181 patients with HFrEF were included in the study. Routine anamnesis, physical examination, laboratory examinations and echocardiography were performed. The LS measurement was performed using the ElastPQ technique. The patients were grouped by NYHA class I-IV. Results: The LS values were significantly different between NYHA class groups, increasing significantly from NYHA class I to IV. The number of patients with LS >7 kPa or >10.6 kPa was significantly greater among the class III-IV patients. The RV myocardial performance index, tricuspid regurgitation pressure gradient, N-terminal pro b-type natriuretic peptide, and aspartate aminotransferase levels were found to be independently associated with LS. It was also observed that LS independently determined III-IV classification and that an increase of 1 kPa increased the risk of being class III-IV by 94.4%. Receiver operating characteristic analysis with a cut-off value of 7 kPa for LS identified patients with class III-IV disease with 82.8% sensitivity and 81.8% specificity. Conclusion: In HFrEF, the LS value increased with NYHA class and independently determined patients with class III-IV disease. A higher LS value independently determined increased RV pressure and systolic functions.